Probiotic therapy on children with allergic rhinitis - Franky Luhulima; IPG Karyana; Sumadiono Sumadiono (Paediatrica Indonesiana, 2013)
phils in nasal secretions of patients with allergic rhinitis may cause persistent nasal blockage. A common therapy for allergic rhinitis is oral or intranasal corticosteroids. However, corticosteroids carry the risk of disrupting growth and development in children. Probiotic treatment in allergic rhinitis patients works by manipulating the bacterial ecosystem of the digestive tract, stimulating the balance of Th1 and Th2 immune responses.Objective To assess the effects of probiotic supplementation on eosinophil levels in nasal secretions, duration of allergic episodes, and total nasal symptom scores in children aged 2-18 years with allergic rhinitis.Methods A randomized, double-blind, controlled trial was performed on children aged 2 to 18 years who visited Sanglah Hospital, Denpasar, between March to July 2012 due to allergic rhinitis. Fifty-five eligible subjects were involved in the study. Subjects were randomly allocated to receive either standard therapy (antihistamines) and probiotics or standard therapy and placebo for 30 days. Mann-Whitney test was used for statistical non-parametric unpaired samples analysis. P values of <0.05 were considered to be statistically significant.Results Fifty-five subjects with allergic rhinitis were randomized into either the probiotic group (27 subjects) or the placebo group (28 subjects). We found that the median (range) nasal eosinophil percentage reduction before the study compared to after 30 days of treatment was higher in the probiotic group than in the placebo group (34 (15-65) vs 6 (0-24) %, respectively, P<0.0001). Median (range) duration of allergic rhinitis episode in the probiotic group was shorter compared to the placebo group (48 (0-96) hours vs 72 (6-168) hours, respectively; P<0.0001). The median (range) total nasal symptom score was also lower in the probiotic group compared to the placebo group (2 (0-3) vs 5 (1-6), respectively; P<0.0001).Conclusion Probiotic supplementation reduces the percentage of nasal eosinophils, duration of allergic rhinitis episode, and total nasal symptoms.